IMPLEMENTASI MEDIA BIG BOOK DALAM KEPANDAIAN MEMBACA SISWA UNTUK TERLAKSANANYA PELAJARAN BAHASA INDONESIA KELAS I SD NEGERI 4 BANDA ACEH - Khadijah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Based on observations, researchers found that some class I students did not appear proficient in reading. So we can see how students' reading methods are disjointed, they are still lacking in pronouncing writing, in fact there are also some students who are still unable to read words and sentences. Therefore, because during the learning process in the classroom students are very based on learning using textbooks which do not attract students' attention and interest in learning. Researchers are very interested in carrying out the learning process using big book media in thematic learning. There is also research carried out so that a teacher is able to find out the influence of big book media on students' reading fluency. The research method for researchers to achieve research is using an experimental method (one group pre-test post-test design). In collecting data, pretest and posttest are used. For better results, this research shows that big book media influences reading fluency for thematic learning. It can be seen and proven by the results of the paired sample T-test with the t experiment, namely (-19.980) in the sig number. (0.000 < 0.03) then shows that the hypothesis (ha) increases and the hypothesis (ho) decreases.